Researching attitudes in school training abstract - Acosta Muñoz, Julio Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2013)
This work is a reflection article, product of the research referred to ‘Researching Attitudes of Young People in Research Training at the School’. The field of interest is focused on developing the contrast, of theoretical and critical type, facing the research training from the proposal of different research attitudes in the training processes of the school. Methodologically, it is constructed from the theoretical review of authors, exploring the problem at the same time. First the difficulties, expressed about the research training and the relationship of this type of education with traditional positivist view, are described. Within the text, it is proposed to visualize different attitudes in the scholar research training (childhood experience, self-knowledge, and the reflective and critical condition), based on the subjectivity of the classroom, placing the trainee as an object of reflection and action in his/her researcher process.